El derecho a la muerte digna: en defensa del suicidio asistido y de la limitación del esfuerzo terapéutico (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This article upholds the right to a dignified death by the limitation of therapeutic effort and to the assisted suicide of imputable and legally mature people which are terminally ill, with minimum life expectancy – also referred as poor prognosis patients –, and those in a persistent vegetative state. Thus, we will reinforce the paradigm shift in medical ethics’ paternalism, analyze the state’s secularism and the triumph of human’s dignity in its sovereign individual protection and the possibility to abdicate the fundamental right to live as a plea to defend the right to a dignified death.
Keywords: The right to a dignified death; assisted suicide; limitation of therapeutic effort; human dignity; sovereign will; abdication of the fundamental right to live